DEPRESI POSTPARTUM DAN KEHARMONISAN RUMAH TANGGA: ANALISIS HUKUM KELUARGA ISLAM BERBASIS STUDI KASUS - Shafa’ Lathifah Zahrah; Ruston Kumaini (USRAH: Jurnal Hukum Keluarga Islam, 2025)
Postpartum depression is a serious psychological disorder experienced by some mothers after giving birth and has the potential to disrupt family harmony. This study aims to analyze the effect of postpartum depression on family harmony and explore prevention efforts in the context of Islamic family law. This study employs a qualitative approach using a case study method involving six postpartum mothers and one clinical psychologist as expert informants. Data collection techniques include literature review and in-depth interviews. The results indicate that postpartum depression is triggered by insufficient mental preparedness, limited social support, and cultural and family environmental pressures. Symptoms include sleep disturbances, unstable emotions, and self-harm impulses. The absence of the husband in providing emotional support is a crucial factor exacerbating the mother's psychological condition. Conversely, spiritual approaches such as dzikir, prayer, and self-reflection have proven to bring inner peace and aid in the recovery process. Islamic Family Law emphasizes the importance of the husband's role in supporting his wife physically and emotionally, as well as upholding the principles of mawaddah wa rahmah within the household. This study recommends the importance of premarital and prenatal education, the husband's involvement in child-rearing, fulfilling the wife's right to support and protection within the household, and collaboration between medical and religious approaches in supporting postpartum mothers.